The Impact of Wroclaw Airport on the Economy of City and Region - Estimation and Analysis of Visitors' Expenditures - Olipra , Łukasz (Studia Oeconomica Posnaniensia, 2016)
In studies of economic impact of air transport on the regional economy, four areas of impact are usually differentiated and distinguished: direct, indirect, induced, and catalytic effects. Direct, indirect, and induced effects define the importance of air transport for the region as one of the sectors of the economy. Stimulated effects are described inter alia as transportation benefits resulting from the operation of the airport in the region, which include, among others, stimulating economic activity, and access to markets through national and international transport links, which are also considered crucial for decisions on investment location in the region. One of the main areas of catalytic impact, in addition to the impact on investment location decisions and economic activity, is considered to be tourism. The aim of this paper is to estimate the size of Wrocław Airport's impact on the economy of the Wroclaw and Lower Silesian regions in terms of expenditures of visitors coming to the city and region by air transport (visitors spending impact). The expenditures of visitors generate additional demand for goods and services in the region, influencing the growth of GDP. The analysis of passengers' expenditures has been broadened by a study of the structure of expenditure according to the type of carrier chosen by visitors and according to the origin of visitors (more precisely, the destination of their return flight). The data necessary to carry out the above analysis were obtained through a survey conducted at Wroclaw Airport in the period March-April 2014, with the use of the CAPI method. Statistical methods were used for the calculations and analysis of the obtained data. The study revealed a strong diversification of the structure of the estimated total expenditure, both according to the type of carrier, and the distinguished origin of visitors (destination of their return flight).